Tourism Development Strategy In Improving The Community's Economy - Muhammad Imran; Adzil Arsyi Sabana; Abdul Wahid Mongkito; Nurjannah Nurjannah; Mahfudz Mahfudz (IAIN Palopo, 2022)
This study aims to see the Berova Beach tourism development strategy in improving the community's economy. The focus of his research is 1) Berov beach tourism development conditions, 2) Berova Coast Tourism Development Impact on Community Economy, and 3) Infrastructure Development Strategies to Support Berova Beach Tourism. In this research, the type of research used is a descriptive qualitative approach. There are two sources of data in this study, namely primary data and secondary data. The data technique was carried out by means of literature study, interviews and observations. The result of this research is that the tourism office of North Kolaka Regency has planned to carry out the processing of Berova Beach tourism in order to have an impact on the socio-economy of the community, such as repairing damaged facilities. For example, swimming pools, docks, and other facilities can increase the attractiveness of tourists to visit Berova beach. By improving facilities and adding new facilities, it will increase the attractiveness of tourists and have a positive impact in increasing the community's economy and regional income in North Kolaka Regency.